Some preliminary findings regarding Kosovo legislation in the field of consumer protection with special emphasis in arbitration clauses in consumers contracts - Plakolli-Kasumi, Luljeta (Array, 2020)
Although the Kosovo Law on Consumer Protection has been harmonized with the EU Directive on Unfair Contract Terms, several inconsistencies are still prevalent in other pieces of legislation, which in turn diminish the effective protection of consumers in line with the aim of the said Directive. The present paper aims at introducing some preliminary findings of the author’s doctoral thesis which can serve as a basis for further improvement of the existing legislation in the field of consumer protection. Full harmonization of the consumer protection legislation with the Unfair Terms Directive entails not only the verbatim transposition of the said Directive into one piece of legislation but an alignment of the entire legislative framework to this end, as well as the development of the court practice in line with the CJEU case-law.